Exploring the Relationship between Critical Thinking Dispositions and Learning Styles in Junior High Science Classrooms - Kamilah, Istahsanah Zulfa; Wahyuni, Sri; Barid, Siti Shofa Assyifaul Qulbi; Astuti, Sri Rejeki Dwi (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2026)
Critical thinking disposition is an essential 21st-century competency in science classrooms, as scientific inquiry requires students to analyze evidence, make observations, and draw conclusions. Students’ understanding of scientific concepts may be influenced by their learning styles—visual, auditory, and kinesthetic—which shape how they process and engage with scientific information. This study aimed to describe students’ critical thinking dispositions, analyze differences based on learning styles, and examine the relationship between the two variables. A quantitative approach was employed, using descriptive and correlational research designs. The research subjects consisted of 31 students from grades VII, VIII, and IX at SMPN 1 Arjasa, selected via simple random sampling. Research instruments included questionnaires on critical thinking disposition and learning styles, each comprising 15 Likert-scale items. Data were analyzed using descriptive statistics and correlational analysis in SPSS version 27. The results show that students’ critical thinking dispositions fall within the high category, and that students demonstrate relatively balanced preferences across visual, auditory, and kinesthetic learning styles. A strong positive relationship was found between learning styles and critical thinking disposition (r = 0.758, p < 0.001). These findings highlight the need for science instruction that incorporates differentiated and multi-modal inquiry approaches to accommodate students’ learning style tendencies and foster the development of critical thinking dispositions.